Expressão de fator de crescimento transformador Beta e inibidores teciduais de metaloproteinases 1 e 2 em próstatas caninas normais e com lesões proliferativas - TOLEDO, Denise Caroline (2012)
The canine gland has drawn interest for research due to its similarities with the human prostate and the great incidence of lesions. Moreover, the canine prostate shows high incidence of diseases. The main lesions that affect the prostate are prostatitis, benign prostatic hyperplasia (BPH), cysts and adenocarcinoma. Recently attention has been given to lesions considered premalignant such as prostatic intraepithelial neoplasia (PIN) and proliferative inflammatory atrophy (PIA), both studied in the human gland and also found in the canine prostate. In order to evaluate the development of prostate cancer starting as premalignant lesions, some immunohistochemical markers are employed, such as tissue inhibitors of metalloproteinases (TIMP), which have a key role in regulating the catalytic action of metalloproteinases (MMP), and transforming growth factor-β (TGF-β), that induces angiogenesis and inhibits cell proliferation and is considered a mediator of prostate growth. The objective of this study was to investigate the expression of TIMP-1, TIMP-2 and TGF-β in canine normal prostate tissue and with proliferative lesions. For this, 150 adult canine prostates were obtained from postmortem examinations. After microscopic evaluation 54 glands, compatible with normal, epithelial BPH, stromal BPH, PIA, PIN and adenocarcinoma were selected and used to make tissue microarray block (Tissue Microarray - TMA). TMA slides were subjected to immunohistochemistry with anti-TIMP-1, anti-TIMP-2 and anti-TGF-β, to assess staining intensity of epithelial cells and stromal cells.Cytoplasmatic staining of canine prostate cells by TIMP-1, TIMP-2 and TGF-β was observed, with TIMP-1 and TIMP-2 being more expressed in premalignant and malignant lesions, while TGF-β was expressed mainly by normal tissue and BPH. Furthermore, there were differences in the expression between epithelial and stromal cells.